Blastogenic response of human lymphocytes to human cytomegalovirus. - Waner, J L (1977)
A method was developed for measuring the blastogenic response of human lymphocytes to human cytomegalovirus (CMV). Viral and control antigens were prepared by extracting disrupted infected and uninfected cell cultures with an alkaline buffer. Lymphocytes from ten donors with complement-fixing (CF) antibody exhibited a blastogenic response, whereas cells from ten seronegative donors did not. A relationship between the stimulation index (SI) and the results of neutralization (NT), indirect haemagglutination (IHA) or CF tests was not observed. The maximum blastogenic response occurred after 5 to 7 days of incubation and was usually greater when the cultures were supplemented with homologous plasma instead of sera. The presence of CMV antibody in the supplementary sera did not appear to affect the reactivity of the lymphocytes.